A dual death/survival role of autophagy in the adult ovary of Lagostomus maximus (Mammalia- Rodentia) - Leopardo, Noelia P. (PLoS One, 2020)
Follicular atresia is a cell death event that occurs in the great majority of follicles before ovulation in the mature mammalian ovary. Germ cell loss has been mainly associated to apoptosis although autophagy also seems to be at play. Aimed to increase our understanding on the possible cooperating role of autophagy and apoptosis in follicular atresia and/or follicular survival, we analyzed both programmed cell death mechanisms in a rodent model, the South American plains vizcacha, Lagostomus maximus. Female vizcacha shows highly suppressed apoptosis-dependent follicular atresia in the adult ovary, with continuous folliculogenesis and massive polyovulation. This strategy of massive ovulation requires a permanent remodeling of the ovarian architecture to maintain the availability of quiescent primordial follicles throughout the individual's reproductive lifespan. We report here our analysis of autophagy (BECN1, LAMP1 and LC3B-I/II) and apoptosis (BCL2 and ACTIVE CASPASE-3) markers which revealed interactive behaviors between both processes, with autophagy promoting survival or cell death depending on the ovarian structure. Strong BECN1, LC3B-II and LAMP1 staining was observed in atretic follicles and degenerating corpora lutea that also expressed nuclear ACTIVE CASPASE-3. Healthy follicles showed a slight expression of autophagy proteins but a strong expression of BCL2 and no detectable ACTIVE CASPASE-3. Transmission electron microscopy revealed a high formation of autophagosomes, autolysosomes and lysosomes in atretic follicles and degenerating corpora lutea and a low number of autophagic vesicles in normal follicles. The co-expression of LC3B-BECN1, LC3B-LAMP1 and LC3B-ACTIVE CASPASE-3 was only detected in atretic follicles and degenerating corpora lutea, while co-expression of BCL2-BECN1 was only observed in normal follicles. We propose that autophagy could act as a mechanism to eliminate altered follicles and remnant corpora lutea providing the necessary space for maturation of primordial follicles that continuously enter the growing follicular pool to sustain massive ovulation.